2012
DOI: 10.1037/a0026700
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in adults in randomized clinical trials of binge eating disorder.

Abstract: Objective Recent studies suggest that binge eating disorder (BED) is as prevalent among African American and Hispanic Americans as among Caucasian Americans; however, data regarding the characteristics of treatment-seeking individuals from racial and ethnic minority groups are scarce. The purpose of this study was to investigate racial/ethnic differences in demographic characteristics and eating disorder symptoms in participants enrolled in treatment trials for BED. Method Data from 11 completed randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 55 publications
8
92
5
Order By: Relevance
“…A thorough search for data appropriate for inclusion was conducted, including a literature search using online databases (e.g., CRISP; Clinicaltrials.gov; PubMed), in order to locate all the studies of BED that met the following criteria: (a) was a randomized, controlled trial; (b) included a psychosocial intervention arm; (c) included > 10 participants overall and presence of participants from African American or Hispanic/Latino racial/ethnic groups; (d) was either published in a peer reviewed journal or funded through a peer review process and; (e) was conducted in the United States (see also Franko et al, 2011, for original report on methods). Fourteen studies were identified through the search, some of which were multi-site studies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A thorough search for data appropriate for inclusion was conducted, including a literature search using online databases (e.g., CRISP; Clinicaltrials.gov; PubMed), in order to locate all the studies of BED that met the following criteria: (a) was a randomized, controlled trial; (b) included a psychosocial intervention arm; (c) included > 10 participants overall and presence of participants from African American or Hispanic/Latino racial/ethnic groups; (d) was either published in a peer reviewed journal or funded through a peer review process and; (e) was conducted in the United States (see also Franko et al, 2011, for original report on methods). Fourteen studies were identified through the search, some of which were multi-site studies.…”
Section: Methodsmentioning
confidence: 99%
“…The Human Subjects Review committees of each of the original data sites, as well as the principal investigators’ institutions (Boston University and Northeastern University), approved the inclusion of data from the original trials in this study. (See also Franko et al, 2011, for additional details. )…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging epidemiological data suggests that binge eating disorder has a less skewed age and gender distribution than anorexia and bulimia nervosa, with an average age at treatment presentation in the mid-40s [29]. For example, Franko and colleagues [30] analyzed aggregate data from 11 completed randomized, controlled trials for BED (N = 1325) and found the average age at treatment was 47.0 years (SD = 10.7) for Caucasians, 45.1 years (SD = 11.4) for African Americans, and 42.7 years (SD = 10.1) for Hispanics.…”
Section: Binge Eating Disorder: Older Age and Male Gendermentioning
confidence: 99%